2008
DOI: 10.1057/gpp.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on Long-term Care Insurance Purchase in France

Abstract: While many theoretical arguments have been proposed to explain the decision whether to purchase long-term care (LTC) insurance, little work has been done to study this phenomenon empirically. This article uses cross-sectional data from the newly developed SHARE (Survey of Health, Ageing, and Retirement in Europe) database to estimate the determinants of the probability of purchasing LTC insurance in France. We show that LTC insurance is purchased not only to preserve bequests and to financially protect familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 11 publications
3
42
1
1
Order By: Relevance
“… In line with Sloan and Norton (), Mellor () and Courbage and Roudaut (), this result also undermines a necessary condition of the so‐called intrafamily moral hazard hypothesis, which is often invoked to explain the lack of systematic purchasing of LTC insurance. Brau and Lippi Bruni () reached a similar conclusion in an application of stated preference approaches to the demand for LTC insurance.…”
supporting
confidence: 57%
“… In line with Sloan and Norton (), Mellor () and Courbage and Roudaut (), this result also undermines a necessary condition of the so‐called intrafamily moral hazard hypothesis, which is often invoked to explain the lack of systematic purchasing of LTC insurance. Brau and Lippi Bruni () reached a similar conclusion in an application of stated preference approaches to the demand for LTC insurance.…”
supporting
confidence: 57%
“…Indeed, in contrast to the notion that family members serve as substitutes for LTC insurance, Mellor (2001) showed for the U.S. that the availability of informal caregivers has no statistically significant effect on insurance purchase. This was confirmed by Courbage and Roudaut (2008) who found for France that the probability of owning LTC insurance increases for those who have a higher probability of receiving informal care should the need arise in the future. In the light of this current research, an explanation of these empirical results could come from the fact that children are involved in the decision to purchase LTC insurance.…”
Section: Resultsmentioning
confidence: 61%
“…1 German studies are found in Breyer (1991Breyer ( ,1992, Buchholz and Wiegard (1992) and Eisen (1992); international studies are found in Courbage and Roudaut (2008), Guille´n and Pinquet (2008), CostaFont et al (2008), Parker and Clarke (1997), Brown and Finkelstein (2007) and Doerpinghaus and Gustavson (2002). 2 Kunreuther (1978).…”
Section: Introductionmentioning
confidence: 99%